2013
DOI: 10.5539/esr.v2n2p34
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Moisture Flux over South and Southwest of Iran: A Case Study from December 10 to 13, 1995 Rain Storm

Abstract: During December 10-13, 1995 a destructive flood occurred over the south part of Iran resulting from the intensive rainfall causing the social and economical damages over that area. This study intends to reveal the main moisture source flux which feeds in the rain fall weather system. The precipitation amount over the study area is four times greater than normal mean in December. The relationships between local atmospheric circulation and moisture flux divergence is investigated for this case of rainfall over s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The mass convergence term is usually the dominant term, and observations have shown that the moisture advection term can significantly contribute to the development and subsequent intensification of storms. By combining the effects of mass convergence as a low-level forcing mechanism with moisture availability, moisture flux incorporates most of the ingredients necessary for convection (Roshani et al 2012).…”
Section: Computation Of Horizontal Moisture Flux and Wind Shearmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass convergence term is usually the dominant term, and observations have shown that the moisture advection term can significantly contribute to the development and subsequent intensification of storms. By combining the effects of mass convergence as a low-level forcing mechanism with moisture availability, moisture flux incorporates most of the ingredients necessary for convection (Roshani et al 2012).…”
Section: Computation Of Horizontal Moisture Flux and Wind Shearmentioning
confidence: 99%
“…These effects depend not only on the sensitivity of populace to climate change but also on their ability to adapt to risks and changes associated with it. Since the atmospheric moisture budget plays an important role in the hydrology of a particular region, the changing weather patterns caused by climate change has increased the incidences of extreme rainfall events (Roshani et al 2012;Weisman et al 1988). Rainfall variability associated with climate change has impacted socioeconomic activities such as agriculture, food security, water resources management, health sector, hydroelectric power generation, and dam management among others in Nigeria (Bello 2010).…”
Section: Introductionmentioning
confidence: 99%